The Effects of the Legislative Vacuum in Administrative Law on Individuals - Ali, Anfal Isam Ali; Al-Makhzoumy, Waleed Mirza Al-Makhzoumy (Journal of Cultural Analysis and Social Change, 2026)
The rationality and methodology of the legal system are linked to the extent of its compatibility with reality and the extent to which it achieves justice. Administrative law is based in its essence on the principle of the administration's subjection to the law, and its rules should guarantee the protection of the rights and freedoms of individuals and the stability of their legal positions. However, practical reality sometimes reveals legislative gaps in those rules, which affect those guarantees. Since administrative activity requires continuity and regularity, this sometimes pushes the administration to act outside the framework of legal texts in light of the legislative gap. This raises several problems related to the extent of the legitimacy of its actions and their impact on destabilizing legal security, undermining individuals' confidence in the state's legal system, and disrupting their legitimate confidence in the decisions issued by the administration. The research concluded with several results, the most important of which is the need to find constitutional and legal mechanisms that preserve the rights of individuals and their legal status in the face of the gap in legislative texts, through the legal organization of the sources of administrative law, so that there is a legislative arrangement of the sources of the legal rule that can be used to address the gap area and in accordance with the principles of the constitution, in addition to codifying the exceptional means to fill the legislative gap temporarily, whether by the administration or the judiciary, so that the scope of their use, their limits and conditions are defined, as well as strengthening the oversight of the administrative judiciary over the actions of the administration in the presence of the gap area, as we believe it is the most effective outlet that will reduce the negative effects of the legislative gap area and its repercussions on individuals, if any.